Science narratives: inspiring participation in large landscape conservation in Australia - Wyborn, Carina, speaker; Unidentified speaker (Colorado State University. Libraries, 2011)
Large landscape 'connectivity conservation' initiatives are rapidly gaining prominence across the world. They are motivated by a desire to halt biodiversity decline and preserve ecosystem processes in the face of climate change and habitat fragmentation. At the heart of these initiatives is the motivation and ability of individuals, agencies and institutions to collaborate across multiple scales, land tenures and land uses. In a reasonably short period of time, proponents of connectivity conservation have launched the concept as front and centre in debates about climate change adaptation in conservation. The phenomenon of connectivity conservation has taken hold in Australia and there are now major connectivity initiatives in every state. Additionally, Australia is in the process of developing a National Wildlife Corridor Policy. Drawing on the concept of ecological connectivity, proponents claim to be 'connecting people' while 'connecting landscapes'. This framing intends to create a positive narrative that engages and inspires a commitment to conservation by placing small-scale interventions in a larger landscape context. This framing demonstrates the power of a science-based concept to bridge normative and scientific domains and create a space for meaningful action at the local scale. The presentation will explore how these 'science narratives' have been mobilised to create a shared imperative for collaboration. As these narratives blur the boundaries between science and values in an effort to inspire collective action, they present an interesting opportunity to examine the diffusion and interplay between science and practice in collaborative conservation.
Presented at the Fall 2011 Center for Collaborative Conservation (https://collaborativeconservation.org/) Special Seminar, "Collaborative Conservation in Practice: Indigenous Peoples and Conservation", September 6, 2011, Colorado State University, Fort Collins, Colorado. This series focused on Indigenous Peoples and Conservation.
Carina Wyborn is a PhD student at the Fenner School of Environment and Society, Australian National University. Her dissertation is examining the interplay between science, values and action in collaborative conservation with a particular focus on large landscape connectivity conservation in Australia and North America. Carina teaches in the Human Ecology program at the Fenner School and is funded by a Land and Water Australia postgraduate scholarship and a top-up scholarship from the CSIRO Climate Adaptation Flagship. She is also a special advisor to the Federal Government National Wildlife Corridors Advisory Committee. Her current visit to the US was funded by a National Climate Adaptation Research Facility collaboration travel grant.
Includes recorded speech and PowerPoint presentation.
Accessibility features: Unedited transcript.
Keywords: ecology; science into practice; connectivity conservation; community; science narrative